Digital Transformation in the Hospitality Sector: Exploring the Role of Technology in Streamlining Hotel Operations: Transformasi Digital Di Bidang Hospitalitas: Menjelajahi Peran Teknologi Dalam Memperlancar Operasional Hotel - Ramadhan, Kemal Zulfikar; Suharto, Bambang (Institut Pariwisata dan Bisnis Internasional, 2024)
Digital transformation has significantly changed the landscape of the hotel industry. With technological advancements, modern hotels are increasingly adopting digital solutions to enhance their operational efficiency. This study explores the role of digital technology in streamlining hotel operations, focusing on the benefits and challenges associated with it. Through case study analysis from several hotels, we examine the implementation of digital-based hotel management systems, the integration of online booking platforms, and the application of technology in various operational areas. The findings indicate that digital transformation can significantly improve efficiency, optimize guest services, and enhance customer satisfaction. However, challenges such as reliance on technological infrastructure and the need for comprehensive employee training must also be addressed. This study provides valuable insights for readers and hospitality professionals on how to effectively leverage digital technology to improve operational performance, offering a deeper understanding of the benefits and challenges of implementing digital innovations in the context of hotel operations.